Comparison between R2CHA2DS2-VASc Score and CHA2DS2-VASc Score to Predict Acute Stent Thrombosis in Patients with After Primary Percutaneous Coronary Intervention - Çağrı Zorlu; Özge Kurmuş (Acta Medica Alanya)
Aim: Acute stent thrombosis (AST) is an important complication resulting from sudden vascular occlusion after stent implantation, especially in patients with ST-segment elevation myocardial infarction (STEMI). It occurs in about 1% of the patients after primary percutaneous coronary intervention. The CHA2DS2-VASc score is easily applied in daily practice and the components of this score are similar to common risk factors of the AST. Chronic renal disease has a hypercoagulable state and this condition is associated with an increased risk of AST in STEMI. Since the CHA2DS2-VASc score is insufficient to assess the risk of AST in patients with renal dysfunction, we aimed to investigate the prognostic significance of the modified score, R2CHA2DS2-VASc score in patients with AST.Methods:This cross-sectional study retrospectively included 56 patients withAST and 1493 patients without AST after STEMI. The CHA2DS2-VASc and R2CHA2DS2-VASc scores were compared between the two groups.Results:The median CHA2DS2-VASc and R2CHA2DS2-VASc scores were significantly higher in the AST group (P <0.001, P <0.001, respectively). The R2CHA2DS2-VASc score ≥2 was used as a predictor of the AST with a sensitivity of 65% and specificity of 89%.Conclusions: The R2CHA2DS2-VASc score is a simple, cheap, and easily accessible score that can predict AST.